Do Consumer Lifestyle, Halal Labels, and Prices affect Purchasing Decisions? - Delia, Desya; Hidayati, Rini; Marhamah, Siti; Zhafiraah, Nazma Riska (SAN Scientific, 2024)
Lifestyles are increasingly modern, and the needs of consumers past and present are clearly different according to the lifestyle adopted by consumers. Currently, consumers follow developments in trends in all aspects of needs ranging from primary needs to secondary needs in accordance with the lifestyle they adopt, namely the halal lifestyle. This research aims to determine the influence of lifestyle, halal labels, and price on the purchasing decisions of Emina cosmetic products. The sampling technique used was Purposive Sampling. The number of respondents in this study was 100 respondents. Data collection was carried out using the Judgment Sampling method with a questionnaire instrument. The data analysis method used is multiple regression analysis, t-test (partial) coefficient of determination. The research results show that: 1) lifestyle has a positive and significant effect on purchasing decisions. 2) the halal label does not influence purchasing decisions. 3) price does not affect purchasing decisions. A managerial implication that may be relevant is lifestyle management. The company can conduct in-depth market research to understand the lifestyle of its target consumers and determine prices and a pricing strategy that suits the Emina cosmetics market segment, including considering consumer price sensitivity.